Plagioclase alteration and equilibration in ordinary chondrites: Metasomatism during thermal metamorphism. (1st January 2022) - Lewis, Jonathan A.; Jones, Rhian H.; Brearley, Adrian J.
Abstract: In ordinary chondrites (OCs), feldspar is present both in chondrules as a primary, igneous phase, and as a secondary phase that results from crystallization of chondrule mesostasis glass during thermal metamorphism. To further understand the chemical and physical conditions prevailing during thermal metamorphism in OCs, we conducted a study of feldspar microtextures and compositions within chondrules, focusing on alteration and equilibration features. We included OCs representing the full metamorphic sequence (petrologic types 3–6) and all OC groups (H, L and LL). Our observations show that primary calcic plagioclase alters to sodalite, scapolite, and nepheline in petrologic types 3.2–3.9, and to albite in types 3.6–5. Plagioclase also develops alteration features such as zoning, micropores, and alteration lamellae in types 3–4. Sodic plagioclase is present in minor amounts as a primary phase, but also forms from the crystallization of chondrule mesostasis glass (types 3.2–3.9), and predominantly through albitization reactions in calcic plagioclase (types 3.6–5). K-feldspar occurs in albite in types 3.6–6 as fine-scale exsolution lamellae and as larger patches. We combine these observations into an overall model of metasomatism during thermal metamorphism in OCs. Hydrous alteration during prograde metamorphism results in most of the alteration and equilibration features we observe in plagioclase. During retrograde metamorphism, high temperature, short duration infiltration of anhydrous, alkali- and halogen-bearing fluids causes incorporation of K into plagioclase that subsequently exsolves. Overall, we show that evidence of metasomatism is present throughout the metamorphic sequence in all the OCs, and thus was a ubiquitous process on all OC parent bodies. Recognition of the effects of fluid activity in OCs of even the lowest petrologic subtypes has important consequences for radioisotope chronometers, such as Al-Mg and I-Xe, that rely on the integrity of phases such as plagioclase and feldspathic mesostasis glass which are highly susceptible to alteration. Furthermore, the presence of aqueous alteration features in OCs implies that the non-carbonaceous chondrite isotopic reservoir must have also had ices and that models of protoplanetary disk evolution must also include the presence of ices in the inner solar system.